Energia solar fotovoltaica: estudo e viabilidade no nordeste brasileiro - Nascimento, Adriana de Souza (2015)
Solar energy has shown promise, environmentally correct and one of the most important sources of renewable energy. The Solar great potential in Brazil and the new rules of the electricity sector favor distributed generation in the country. Soon, the energies from the photovoltaic cells see experiencing strong growth with regard to technology and progress in the world. Contributing to this, recently, the resolution 482, issued by ANEEL in April 2012 is taken as a big stimulus serving as first step to advance the incentive programs the electrical energy sources; This standard encourages and establishes the General conditions for the access of micro and mini distributed generation and gives the consumer's right to make use, at its discretion, to one of the types of this generation. This policy tends to stimulate the small generators and totally changes the panorama of the Brazilian electric sector, because it allows the access to generation at all levels of the production chain of the electric sector (distribution, sub-transmission lines and transmission), and can be a booster for solar generation in the country. This research project aimed to study and analyze the feasibility of the use of photovoltaic solar energy in Northeast Brazil, presenting the main challenges related to implementation, advantages, demonstrating how the changes in the regulatory environment have influenced the evolution and development of solar generation in the country. The methodological procedure that led this research was the multicase study: through the EVTE based on indicators of investment analysis. The survey was conducted in three distinct segments, with Central: 117, 6kWp, 352, 8kWp and 1Mw respectively. In conclusion, this study showed that the benefits of the integration of solar energy in the Brazilian electric matrix promote sustainable development and clean energy generation competitively, within the new context of the electric sector, and currently is completely viable to invest in this technology.